Mechanism of fracturing fluid damage and experimental study on water lock release of SC-CO2 in tight feldspathic sandstone reservoir - WANG Juanjuan; WANG Junjian; ZHANG Chong; DONG Chuanrui; GE Di (Youqi dizhi yu caishoulu)
In view of the low flowback rate and poor gas well productivity in tight sandstone reservoirs of Shahezi Formation in the JS-LS gas field， Songliao Basin， the mechanism of fracturing fluid damage and water lock release of supercritical carbon dioxide （SC-CO2） in tight feldspathic sandstone reservoirs were analyzed based on the results of core displacement experiment， mineral composition analysis， wettability test， and microscopic analysis. The results showed that the reservoir lithology of Shahezi Formation in the study area is a typical tight feldspathic sandstone， whose smaller pore size and strong hydrophilicity lead to the obvious retention of fracturing fluid after invasion. The average irreducible water saturation is 60.51%， corresponding to an average liquid film thickness of 373.31 nm. The irreducible water and liquid film occupy a lot of pore space. The water lock damage rate accounts for 55.54% of the total damage rate of permeability. This results in fracturing fluid damage， mainly in the form of a water lock. SC-CO2 is significantly different from conventional pre-liquid N2 in terms of removing the water lock due to the strong diffusivity， penetrating ability， and high solubility in water. Moreover， SC-CO2 dissolves into water under high pressure and forms carbonic acid. It dissolves reservoir minerals by extraction， then improving reservoir permeability. In addition， it forms a miscible phase with water and eliminates interfacial tension. Compared with N2 and natural gas， SC-CO2 significantly reduces capillary force in the process of displacement， expands the irreducible water volume in the core， destroys the liquid film， and reduces the irreducible water saturation and the liquid film thickness. It reduces the average irreducible water saturation to 26.754% and the average liquid film thickness to 179.35 nm. Moreover， SC-CO2 can enter almost any pore throat larger than the diameter of CO2 molecules in the reservoir， further enhancing its ability to release water lock.